Struktur Frasa Adverbial Bahasa Batak Toba Analisis Teori X-Bar - Sidabalok, Dindasari; Mulyadi, Mulyadi (Aksara: Jurnal Bahasa dan Sastra, 2024)
This study aims to describe the structures forming an adverbial phrase in the Batak Toba language. This research is a qualitative research. The data in this study is in the form of Batak Toba text. Data sources are obtained through observation, interviews, as well as using researchers' intuitive data as active speakers of Batak Toba language. At the observation stage, researchers were directly involved in the conversations of several Toba Batak speakers in a coffee shop. Then an unstructured interview was conducted using provoking questions to the informant. The type of question given is related to the grammatical acceptability of phrase structure in the Batak Toba language. While in the process of data analysis is carried out by grouping data based on the similarity of elements, then determining the right elements is carried out. The results of research and discussion show that in the Toba Batak language there are 4 rules of adverbial phrase structure in the Toba Batak language, yaitu: (1) Adv + A = Adv’, Adv’ + Spes = FAdv, (2). A + Adv = Adv’, Adv’ + Spes = FAdv, (3) Ad + Adv = Adv’, Adv’ + V = Adv’, Adv’ + Spes = FAdv, (4) Adv + Ad = Adv’, Adv’ + Adv = Adv’, Adv’ + Spes = FAdv.Keywords: adverbial pharase, Tobanese, X Bar theory